Uncovering pathological mechanisms underlying Batten disease : from yeast to more complex models systems - Osório, Nuno Miguel Sampaio (2009)
Tese de doutoramento em Ciências da Saúde (ramo do conhecimento em Ciências Biológicas e Biomédicas)